Investigation of bacteremia following orthodontic debanding - (:unkn) unknown (My University, 2000)
The aim of this study was to investigate the prevalence of bacteremia after orthodontic debanding and debonding. The study group comprised 30 patients (10 men, 20 women). All were treated using the Edgewise technique. Patients with acceptable oral hygiene and fixed appliances in both jaws were included in the study group. Blood samples were obtained using a strict aseptic technique before and after removal of bands and brackets. A 6.6% bacteremia prevalence was observed in both preoperative and postoperative blood samples.
Keywords: Adult; Female; Humans; Prevalence; Adolescent; Male; Follow-Up Studies; Bacteremia; Oral Hygiene; Tooth Movement Techniques; Blood; Colony Count, Microbial; Dental Debonding; Orthodontic Appliances; Streptococcal Infections; Streptococcus; Streptococcus sanguis